If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Ln(2x + -6) + 5 = 6 Reorder the terms: nL(-6 + 2x) + 5 = 6 (-6 * nL + 2x * nL) + 5 = 6 (-6nL + 2nxL) + 5 = 6 Reorder the terms: 5 + -6nL + 2nxL = 6 Solving 5 + -6nL + 2nxL = 6 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -6nL + -5 + 2nxL = 6 + -5 Reorder the terms: 5 + -5 + -6nL + 2nxL = 6 + -5 Combine like terms: 5 + -5 = 0 0 + -6nL + 2nxL = 6 + -5 -6nL + 2nxL = 6 + -5 Combine like terms: 6 + -5 = 1 -6nL + 2nxL = 1 Reorder the terms: -1 + -6nL + 2nxL = 1 + -1 Combine like terms: 1 + -1 = 0 -1 + -6nL + 2nxL = 0 The solution to this equation could not be determined.
| -4.2u+5.5=5.4u-4.1 | | 3(4x+5)-5(2x+3)=22 | | Ln(2x-6)-5=5 | | 5[3y+12]=6[5y+20] | | H=-5t^2+40t+10 | | -128+9p=3p-27 | | -2x-3zx=1-10y | | -128+9p=-3p-27 | | 2x+27x+15= | | 4*-7=41 | | y=15-4i | | 4(Y+22)+1=-5(3-2Y) | | 2(2a+4)-3(a-1)=14 | | 2x+7x+15= | | 5x-(9x+2)=5x-11 | | 2x-8-4x+5=5x+7-3x-10 | | f(x)=x^2-2x+15 | | 9x^2-147x-102= | | 1x+2y(5r)= | | 3x^2-147x-102= | | 8+6p=20 | | 10-p=4 | | 5x-6=12x+62 | | (5x+5)=(3x+5) | | -8x+4=-19x+48 | | 27+53=4x | | (x+8)(x-2)(x+3)(x+2)=0 | | 0.3(2z+7)+2.9=0.5(2z-6) | | 44x^2-30xy+4y^2=0 | | 9x-9=-24x+288 | | -6x+1=10x-47 | | xy-7x=3y |